Students' perspectives on raising achievement through inclusion in Essunga, Sweden. Issue 1 (2nd January 2016) - Allan, Julie; Persson, Elisabeth
Abstract : A Swedish municipality that has transformed its position at the bottom of the national school league tables to top within three years – through inclusive education – has attracted much attention both in Sweden and internationally. This article offers the students' perspectives on the transformation and how they have experienced success. A social capital framework was used to interpret the students' perspectives and experiences and revealed the strong norms and values to which the students were exposed and the bonding, bridging and linking practices which connected them to one another. The students articulated a strong commitment to the norms and values relating to personal goal achievement and success but also to helping other students to succeed and conveyed a clear understanding and confidence about themselves as learners. The outcomes in Essunga, of raised achievement through an inclusive orientation, are significant in the context of what has been called a new policy hegemony operating in Sweden and elsewhere, whereby commitment to democratic ideals continue to be voiced while inequalities surface through new discursive practices.